Investigating the Relationship between Magnesium levels and Diabetes Mellitus in Pregnant Women - Musavi, Hadis; Mohammadi Tahroodi, Fariba; Fesahat, Farzaneh; Bouzari, Zinatossadat; Esmaeilzadeh, Seddigheh; Elmi, Fatemeh; Yazdani, Shahla; Moazezi, Zoleika (International journal of molecular and cellular medicine, 2019)
Gestational diabetes mellitus (GDM) is defined as one of the three main types of diabetes mellitus (DM). It is established that GDM is associated with exceeding nutrient losses owing to glycosuria. Magnesium (Mg), as one of the essential micronutrients for fetus development, acts as the main cofactor in most enzymatic processes. The aim of this study was to measure serum and cellular levels of Mg, albumin, creatinine, and total protein to further clarify the relationship between these components and DM in pregnant women. Blood samples were obtained from 387 pregnant women. The participants were classified into four groups based on their type of diabetes, namely GDM (n=96), DM (n=44), at high-risk of DM (n=122), and healthy controls (n=125). All participants' fasting blood sugar (FBS), creatinine, albumin, Mg, and total protein in the serum levels and red blood cell Mg (RBC-Mg) were measured during 24-28 weeks of gestation. Groups were compared for possible association between DM and abortion, gravidity, and parity. The serum levels of creatinine, FBS, albumin, Mg, and RBC-Mg were statistically different among four groups (P =0.001). Significant lower levels of RBC- Mg was observed in all studied groups in comparison with controls. Given a positive correlation between DM and abortion, it seems that decreased levels of RBC-Mg and serum albumin can increase the risk of abortion in pregnant women. Our data demonstrated significant alterations in albumin, Mg, and creatinine concentrations in women with DM or those at high risk of DM during their gestational age. It seems that the measurement of these biochemical parameters might be helpful for preventing the complications, and improving pregnancy outcomes complicated with DM.